Cassava agronomy research and adoption of improved practices in India: Major achievements during the past 30 years - George, James; Mohankumar, C.R.; Nair, G.M.; Ravindran, C.S. (International Center for Tropical Agriculture, 2001)
Over the past 25-30 years, cassava agronomy research in India has made tremendous progress. In the recent past there has been a steady increase in the cultivation of cassava in nontraditional areas, despite the fact that cereals form the major crop and staple food of the country. There has been a marked increase in the number of cassava-based industries in states like Tamil Nadu and Andhra Pradesh, which is responsible for the expansion of the area under cassava in those states. Compared to 1980/81 the cassava area in Andhra Pradesh increased by 40% and in Tamil Nadu by 34%. In the state of Kerala, where cassava is traditionally grown for food, the cassava area decreased considerably (46%) due to farmers’ preference for more remunerative plantation crops like rubber and coconut. A shift in the traditional cropping pattern, however, could also be noted in Kerala where rice in the lowlands is now being replaced by cassava, as the latter produces more income than the former. The yield of cassava has been almost static in the range of 19 to 23 t/ ha in Kerala, about 7 to 10 t/ha in Andhra Pradesh, and 36-37 t/ha in Tamil Nadu, which has the highest yield in the world. Extensive research on cassava’s nutritional requirements, agro-techniques, cropping systems and a long-term fertilizer trial have been conducted during the past three decades. Under rainfed conditions the best time of planting was found to be April-May; however, under irrigated conditions, it can be planted during any part of the year. Pit followed by mound has been identified as the best method for planting cassava stakes, using a spacing of 90x90 cm. Removing all but two healthy shoots on opposite sides of the stem has been found to increase yields. Investigations on the use of cassava plants as an alternate source for rearing eri silk worms revealed that the cassava root yield was adversely affected by this practice. Irrigating the crop at 25 per cent available soil moisture depletion level during the growth period could double the root yield. Supplementary irrigation at IW/CPE ratio=1.0 increased the root yield by 90 per cent over the rainfed crop. Continuous application of NPK fertilizers did not significantly effect soil pH, but the available nutrient status of the soil was considerably enhanced, while the build-up of P was excessively high. An appreciable increase in the soil pH (4.7 to 6.1) was noticed in the treatment that received continuous applications of wood ash. Organic carbon content of the soil was found to increase in the plots that received farm-yard manure (FYM). When chemical fertilizers were applied regularly, the Cu and Zn status of the soil declined, but these deficiencies were not observed in plots that received FYM in addition to NPK. It was further revealed that the N and K requirement of the crop was in the ratio of 1:1. Liming at a rate of 2 t CaO/ha was found to be effective in increasing root yields in very acid soils. Application of sulfur resulted in an increase in starch and a decrease in the HCN content of roots. Significant responses to soil application of the micronutrients Zn, B and Mo were also observed. Cropping systems research has shown that short-duration (seven months) cassava varieties can be grown successfully in a rice-based cropping system. Cowpea and groundnut were found quite remunerative as intercrops in cassava. Incorporation of cowpea as green manure in situ at time of planting cassava was found to be as effective as the application of FYM; in addition, it also reduced the N requirement by 50%.